2014
DOI: 10.1163/22134808-00002449
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Parietal Cortex in Multisensory and Response Integration: Evidence from Transcranial Direct Current Stimulation (tDCS)

Abstract: The question of how the brain forms unified representations from multisensory data that are processed in distinct cortical regions is known in the literature as 'the binding problem'. In the last decade, several studies have suggested possible neural mechanisms and brain regions that might be involved in integration processes. One of the brain regions that is implicated with multisensory perception is the posterior parietal cortex (PPC). Evidence from patients with parietal lesions suggests the involvement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Similarly, anatomical connectivity indicates that this brain area is a convergent hub of auditory, somatosensory, and visual motion systems59. Indeed, applying anodal transcranial direct current stimulation over the right PPC prevented the multisensory integration of visual and auditory features6061. Furthermore, clinical reports have demonstrated that PPC lesions cause feature-binding deficits62.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, anatomical connectivity indicates that this brain area is a convergent hub of auditory, somatosensory, and visual motion systems59. Indeed, applying anodal transcranial direct current stimulation over the right PPC prevented the multisensory integration of visual and auditory features6061. Furthermore, clinical reports have demonstrated that PPC lesions cause feature-binding deficits62.…”
Section: Discussionmentioning
confidence: 99%
“…Other work has applied anodal tDCS to visual areas and improved perceptual learning [62], while parietal tDCS has improved reaction time on contralateral search tasks [63]. However, another body of research has found that both right anodal and cathodal tDCS on DLPFC impair the efficiency of managing stimulus-response feature bindings, which taxes perceptual abilities; this study proposed that tDCS could create reversible ‘frontal lesions’, for at least specific cognitive tasks [64, 65]. Another study found that anodal and cathodal tDCS over medial-frontal cortex did not change perceptual processing, but only subsequent error- and feedback-related negativities [66].…”
Section: Discussionmentioning
confidence: 93%
“…The role of the PPC in multisensory integration of other modalities was also manifest in a study by Pasalar, Ro, and Beauchamp (2010), where TMS over the PPC interrupted visual-tactile integration. In addition, Zmigrod (2014) has found that tDCS delivered to the right PPC disrupts audio-visual integration, and Bolognini et al, 2010 have illustrated that anodal tDCS delivered to the right, but not left, PPC helps to facilitate performance on an audio-visual exploration training task. Thus, the current findings offer additional evidence for the causal relationship between the right PPC and the temporal binding window.…”
Section: Discussionmentioning
confidence: 99%
“…The active electrode was placed over either P4, P3, or F3 (depending on the participant's stimulation group), a location atop the right PPC, left PPC, and the left DLPFC respectively, according to the international 10-20 system for EEG electrode placement. The reference electrode was placed over the contralateral supraorbital area as this montage has been proven to be effective in neurostimulation studies involving multisensory perception (Bolognini, Fregni, Casati, Olgiati, & Vallar, 2010;Bolognini & Maravita, 2011;Zmigrod, 2014;Zmigrod et al, 2014) and other cognitive functions (Cerruti & Schlaug, 2009;Javadi & Walsh, 2012;Metuki, Sela, & Lavidor, 2012; for review see Nitsche et al, 2008). The stimulation lasted 15 min with a constant current of 2 mA and with a 15-s fade-in and fade-out.…”
Section: Experimental Design and Stimulation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation